The Effect of Switching the Order of Experimental Teaching in the Study of Simple Gravity Pendulum – A Study with Junior High-school Learners - Tsihouridis, Charilaos; Vavougios, Dennis; Ioannidis, George (International journal of emerging technologies in learning, 2017)
The present study focuses on the educational value of lab work while teaching and learning Physics. Specifically, it investigates and compares the learning outcomes between three different experimental groups, in the study of the Simple Gravity Pendulum in the lower secondary school, using a sample of 61 students aged 14-15. The first group comprising 25 students practiced first on virtual and then on real lab, while the second group of 24, first on real and then on virtual lab (change of order in the tasks).An additional third group, involving 12 students, used sensors and data loggers during experimental practice. The educationally optimum order of use of such labs is investigated herein. The learners exploited the capabilities of the lab equipment, in that they themselves designed, constructed, and analysed the simple gravity pendulum. The focus in the teaching and learning of the pendulum was on examining subject relevance in the context of everyday applications, the independency of the period from the mass of the bob, or the amplitude, and the dependence of the period from the pendulum length, and the local acceleration of gravity. The research tools used were a stabilised questionnaire, with 16 closed-type questions and 7 questions asking for a justifying answer, in addition to a semi-structured interview. Data were taken and were appropriately analysed and compared, and conclusions are presented herein. The results confirmed that concerning some teaching objectives, learners’ understanding is positively affected by the order the real and the virtual labs are used in teaching. This result applies when addressing this age-group, and when teaching the simple gravity pendulum